PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN POC LIDAH BUAYA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) - Dony Dwi Prasetyo; Srie Juli Rachmawatie; Pramono Hadi (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
This study aims to obtain the best concentration of aloe vera POC on the growth and yield of cucumber plants, to determine the time interval of giving the best aloe vera POC to the growth and yield of cucumber plants, and to determine the effect of the interaction of concentration and frequency of aloe vera POC on the growth and yield of cucumber plants. . This research was carried out from March 2022 to April 2022 in Hamlet Kepoh, Tohudan Village, Colomadu District, Karanganyar Regency. This study used the Completely Randomized Block Design (RAKL) method which consisted of two factors. The first factor is the time interval of giving aloe vera POC (I) which consists of 3 levels. The second factor is the concentration of aloe vera POC solution (K) which consists of 4 levels of analysis of variance analysis with the F test or diversity test at the level of 5% and 1%. If each treatment was significantly different, it was continued with the Duncan Multiple Range Test (DMRT) at 5% level. The results of this study indicate that the time interval treatment of aloe vera POC (I) showed the best effect on the parameters of observing the number of fruits (2.42), fruit length (20.83 cm), dry bean weight (38.33 g), weight fresh chestnut (254.17 g) and root length (43.84 cm). The treatment of aloe vera POC concentration (K) showed the best effect on the parameters of the fresh weight (261.11 g). The interaction between concentration and time interval of aloe vera POC administration (I X K) showed the best effect on the observed parameters of root length (50 cm).